Công tác phục vụ bạn đọc tại Thư viện Học viện Chính trị Quốc gia Hồ Chí Minh : Khóa luận tốt nghiệp - Nguyễn, Thị Tuyết Vân (2000)
Công tác phục vụ bạn đọc tại Thư viện Học viện Chính trị Quốc gia Hồ Chí Minh.